2001
DOI: 10.1046/j.1365-3121.2001.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and magnitude of displacement on the Altyn Tagh fault: constraints from stratigraphic correlation of adjoining Tarim and Qaidam basins, NW China

Abstract: The Altyn Tagh fault plays an important role in growth of the north‐western Tibetan plateau, but the timing of its inception and magnitude of left‐lateral displacement are not well constrained. This study provides new independent constraints by correlating stratigraphic development and spatial distribution of the neighbouring Tarim and Qaidam basins. It is shown that the Tarim and Qaidam basins experienced quite similar stratigraphic and sedimentary evolution from late Sinian to early Palaeogene times. This fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 28 publications
1
39
1
1
Order By: Relevance
“…Our study does not support the view that the Altyn Tagh fault as the northern boundary fault of the Qinghai-Tibetan Plateau went into the Alxa Block during the Early Cenozoic, Specific reasons are as follows: À many researchers have shown that as the northern boundary of the plateau, the movement of the Altyn Tagh fault began in the Oligocene (Yin et al 2002;Meng et al 2001;Yue and Liou 1999;Yue et al 2001a, b);`Although some workers have argued that the Altyn Tagh fault entered the Alxa Block, there was not very convincing evidence; not only were the paths of the Altyn Tagh fault in the Alxa Block of different workers divergent, but also there were controversies about the amount of displacement and active time, for example Yue and Liou (1999) suggested that the Altyn Tagh fault linked with the Engeerwusu fault along the northern boundary of the Alxa Block and went into southeast Mongolia; Darby et al (2005) and Webb and Johnson (2006) considered that the Altyn Tagh fault should connect with the Yabulaishan fault in the Alxa Block, and further linked it with the Zuunbayan fault in southeast Mongolia. However, Johnson (2004) found that the Zunnbayan fault was not active after the Cretaceous;´although there are many current debates about estimates of displacement of the Altyn Tagh fault (RGAATFS, SSB 1992;Meng et al 2001;Yin et al 2002;Wang 1997;Yue and Liou 1999;Yue et al 2001a, b), the fact that the displacement on the western and central parts of the fault was larger than that on the eastern part has been accepted by most workers, in other words, the activity on the fault became weaker to the northeast.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Our study does not support the view that the Altyn Tagh fault as the northern boundary fault of the Qinghai-Tibetan Plateau went into the Alxa Block during the Early Cenozoic, Specific reasons are as follows: À many researchers have shown that as the northern boundary of the plateau, the movement of the Altyn Tagh fault began in the Oligocene (Yin et al 2002;Meng et al 2001;Yue and Liou 1999;Yue et al 2001a, b);`Although some workers have argued that the Altyn Tagh fault entered the Alxa Block, there was not very convincing evidence; not only were the paths of the Altyn Tagh fault in the Alxa Block of different workers divergent, but also there were controversies about the amount of displacement and active time, for example Yue and Liou (1999) suggested that the Altyn Tagh fault linked with the Engeerwusu fault along the northern boundary of the Alxa Block and went into southeast Mongolia; Darby et al (2005) and Webb and Johnson (2006) considered that the Altyn Tagh fault should connect with the Yabulaishan fault in the Alxa Block, and further linked it with the Zuunbayan fault in southeast Mongolia. However, Johnson (2004) found that the Zunnbayan fault was not active after the Cretaceous;´although there are many current debates about estimates of displacement of the Altyn Tagh fault (RGAATFS, SSB 1992;Meng et al 2001;Yin et al 2002;Wang 1997;Yue and Liou 1999;Yue et al 2001a, b), the fact that the displacement on the western and central parts of the fault was larger than that on the eastern part has been accepted by most workers, in other words, the activity on the fault became weaker to the northeast.…”
Section: Discussioncontrasting
confidence: 87%
“…However, Johnson (2004) found that the Zunnbayan fault was not active after the Cretaceous;´although there are many current debates about estimates of displacement of the Altyn Tagh fault (RGAATFS, SSB 1992;Meng et al 2001;Yin et al 2002;Wang 1997;Yue and Liou 1999;Yue et al 2001a, b), the fact that the displacement on the western and central parts of the fault was larger than that on the eastern part has been accepted by most workers, in other words, the activity on the fault became weaker to the northeast. As in the above analysis, the Alxa Block lacks obvious coeval deformation, and the latest deformation (Pleistocene) only occurred along the margins of the block;…”
Section: Discussionmentioning
confidence: 99%
“…The earliest anatexis both at the hanging wall and footwall of the STDS in the Himalaya collisional belt occurred at 35 Ma, indicating that ~35 Ma partial melting may be the major factor to initiate the STDS and in turn leads to tectonic transition from compressive shortening to extension. Within the Tibetan plateau and adjacent areas, initial movement of the Karakorum Fault [51], large displacement along the Altyn Tagh fault [52,53], strike-slip movements in the Red River belt [54], and aridification of the Tibetan plateau linked to global cooling [55] all occurred at ~35 Ma. All these studies indicate that ~35 Ma tectonic events in the Tibetan plateau are widespread.…”
Section: The Implication Of Melting In Paiku Composition Leucogranitementioning
confidence: 99%
“…Ritts and Biffi (2000) estimated an offset of 400 ± 60 km based on the restoration of Jurassic lake shorelines. Meng et al (2001) chosen Early Palaeozoic and Late Triassic suture zones within the East and West Kunlun and pinch-outs of Mesozoic strata as piercing lines and estimated offsets of 380 and 350-400 km, respectively. Chen et al (2004) suggested that slipping along the central Altyn Tagh Fault began in the Early Oligocene based on the Cenozoic sedimentary record.…”
Section: Offset Of the Assfmentioning
confidence: 99%
“…In recent years the Altyn Strike-Slip Fault (ASSF) has been become a hot-spot for Tibetan Plateau geological research. A large amount of research work related to the ASSF have been carried out, predominantly dealing with radiometric isotope age dating (Liu et al, , 2001bSobel and Arnaud, 1999;Zhang et al, 2000Chen et al, 2001Chen et al, , 2002bChen et al, , 2003Jolivet et al, 2001;Sobel et al, 2001;Wang et al, 2001;Li et al, 2002;Cowgill et al, 2003;Yue et al, 2004) and the reconstruction of tectonic belts on both sides of the ASSF and estimations of the amount of offset (Cui et al, 1997;Guo et al, 1999;Cowgill et al, 2000;Delville et al, 2001;Meng et al, 2001;Sobel et al, 2001;Yang et al, 2001;Yue et al, 2001;Ge et al, 2002;Arnaud et al, 2003;Jolivet et al, 2003). An estimate of cumulated offset 350-400 km along the ASSF has been accepted by most of researchers, but the age of initiation of the ASSF is still the subject of dissention.…”
Section: Introductionmentioning
confidence: 99%